Analysis of the Quality of Facilities and Infrastructure on Student and Lecturer Satisfaction in Private Higher Education Institutions: Analisis Kualitas Sarana dan Prasarana terhadap Kepuasan Mahasiswa dan Dosen pada Perguruan Tinggi Swasta - Restiawati, Yanti; C.O.M, Nancy; Dwiyono, Yudo (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This research aims to analyze the relationship between the quality of facilities and infrastructure and the satisfaction levels of students and lecturers in Private Higher Education Institutions (PTS). Based on a satisfaction survey conducted, it was found that 78% of students in PTS with complete facilities reported high satisfaction levels, compared to 54% in PTS with limited facilities. The study identifies aspects of user satisfaction, including physical comfort, functionality, aesthetics, and the relevance of facilities to academic needs. Data from 50 respondents indicate that the availability of flexible learning spaces and adequate technological facilities are critical factors. Differences in funding sources and government policies significantly contribute to the disparity in facility quality between the two types of higher education institutions. The enhancement of facilities and infrastructure is not only aimed at increasing student and lecturer satisfaction but also at strengthening the institution's competitiveness in the education market. PTS needs to establish partnerships with the private sector and seek external funding to support facility development. Furthermore, a data-driven approach in policy formulation is expected to create a conducive academic environment that supports improved academic performance. By understanding the factors influencing user satisfaction, institutions can design appropriate strategies to enhance the quality of facilities and infrastructure, thereby benefiting all stakeholders in higher education